The bicycling big book of cycling for beginners everything a new cyclist needs to know to gear up and start riding - Bortman, Tori (Emmaus, Pennsylvania Rodale Books, 2014)
"the indispensable, must-have guide for anyone looking to gear up and start pedaling. Bicycling is undergoing a renaissance in this country as millions of people are taking to the streets in this nostalgic, beloved pastime. From purchasing one's first bike to learning all its different components, Bicycling Big Book of Cycling for Beginners is the go-to guide for any beginning cyclist's collection. The vast territory of cycling and its facets will become a welcome terrain for any rider who wants to ride smarter, faster, and safer using this incredible wealth of knowledge. As the sales of new bicycles increase every year, these helpful tips will educate and inform beginning cyclists so they perform to their maximum potential, all while having fun. Trusted bicycle consultant Tori Bortman distills the essentials every beginning cyclist needs to know. She covers different types of rides, the components of bicycles, proper cycling clothing and equipment, basic road skills, nutrition, training, maintenance, and how to ride for a cause. She also explores how to approach cycling from the conceptual beginnings into tangible, real-time facts about riding as a new cyclist, as well as elaborating on the bountiful health benefits of cycling, including weight loss, stress reduction, and boosted immunity. This is the ultimate guide to bicycling know-how for beginning cyclists"--
Includes index.
Keywords: Cycling -- Handbooks, manuals, etc